2021
DOI: 10.3389/fgene.2021.650416
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Related Gene-Based Prognostic Model and Immune Infiltration in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of the most common tumors in the urinary system. Ferroptosis plays a vital role in ccRCC development and progression. We did an update of ferroptosis-related multigene expression signature for individualized prognosis prediction in patients with ccRCC. Differentially expressed ferroptosis-related genes in ccRCC and normal samples were screened using The Cancer Genome Atlas. Univariate and multivariate Cox regression analyses and machine learning methods were emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
(78 reference statements)
0
18
1
Order By: Relevance
“…According to our results, high methylation score is associated with high methylation of cg15044146 in ACACA, which results in resistance to ferroptosis and poor prognosis. This is inconsistent with previous studies (33,34). ZEB1 is an epithelial-mesenchymal transition (EMT) regulator as well as a lipogenic factor, could suppress GPX4 depletion- induced ferroptosis (35).…”
Section: Discussioncontrasting
confidence: 83%
“…According to our results, high methylation score is associated with high methylation of cg15044146 in ACACA, which results in resistance to ferroptosis and poor prognosis. This is inconsistent with previous studies (33,34). ZEB1 is an epithelial-mesenchymal transition (EMT) regulator as well as a lipogenic factor, could suppress GPX4 depletion- induced ferroptosis (35).…”
Section: Discussioncontrasting
confidence: 83%
“…In addition, we constructed a scoring system to quantify the ferroptosis pattern of each CCs patient, defined as FS, to guide individualized prognostic analysis and precise treatment of CC. Studies have shown that an FRG-based prognostic nomogram could improve the estimation of the survival rate of patients with clear cell renal cell carcinoma ( 50 ). Similarly, a novel ferroptosis risk signature could be useful in predicting prognosis and reflecting immune infiltration in adrenocortical carcinoma ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it may release some immunogenic substances to activate the immune system and thus inhibit tumor growth [ 41 ]. Mast cells can enhance T cell-mediated immune responses, and the number of mast cells in the TME has been reported to correlate with reduced cancer progression and improved survival [ 42 ]. Dendritic cells are heterogeneous, intrinsic immune cells that can infiltrate and process tumors and play a key role in triggering antitumor T-cell immunity by providing tumor-derived antigens to naive T cells, and are major therapeutic targets for tumor immunotherapy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%